Congestion control in vehicular adhoc network: a survey - Shamsul Jamel Elias; Shahirah Mohamed Hatim; Mohamad Yusof Darus; Shapina Abdullah; Jamaluddin Jasmis; R. Badlishah Ahmad; Adam Wong Yoon Khang (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Vehicular adhoc network (VANET) has a significant potential in reducing traffic congestion to provide a stress-free and safer platform for road drivers to travel on the road. However, the current VANET is vulnerable to several challenges which need to be overcome. Congestion control is considered as one of the main challenges in VANET due to the high dynamic topology characteristic. Reliable congestion control (CC) are necessary to provide effectient dissemination of time-critical safety messages in VANET applications; safety and non-safety applications. In this paper, we present the overview on VANET, its application and challenges. We also discuss on the congestion control and provide a brief survey on the congestion control algorithms such as vehicular cloud computing, multiplicative rate decreasing algorithm, multi-objective Tabu search, D-FPAV algorithm and beaconing strategies which have been proposed in order to provide better solutions towards achieving a successful Smart Tranporation System.